The Analysis of The Influence of Monetary Indicators on Financial System Stability in Indonesia - Ahmad Fadlan; Rahmad Sembiring; Ira Gretti Hutagalung (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
The money supply can affect other economic variables, such as output and prices, create stability in the economy and help achieve the ultimate goal of monetary policy, namely the stability of inflation and exchange rates. The level of the exchange rate by the monetary authority must be kept stable because an unstable exchange rate, especially one that experiences a sharp depreciation, can have financial crisis implications. This research approach was associative/quantitative research. The data used in this study are secondary data taken and processed from Bank Indonesia (BI) and the Central Statistics Agency (CSA) from 2013-2023 (11 years). Based on the results of regression analysis shows that the variable money supply, exchange rates, and interest rates simultaneously affect the inflation variable. Based on the results of regression analysis shows that the variable money supply has a positive and significant effect on inflation. Based on the results of regression analysis, the exchange rate variable has a negative and significant effect on inflation. Based on the regression analysis, the interest rate variable has no statistical effect on inflation.